The Prohibition of Salary (in Particular) and Economic Content(in General) of Collective Bargaining in Public Employment: An Exercise of Evaluation of Judicial Reasoning - Sánchez Reyes, Christian (2016)
From a jurisprudential analysis of several judgments of the Constitutional Court, the author tries to show a new perspective based on a dynamic vision of a Social State and Constitutional Law, which ones require a fundamental presence of judges in the deliberation of court cases related to the prohibition on collective bargaining in the case of public employment, in order to show the scope of axiological protection that labor law should take in situations such as public employment and lack of funds in order to achieve equality between public and private employment , thus avoiding overt discrimination.